Labour Markets for and Working Conditions of Turkish Seafarers: An Exploratory Investigation - (:unkn) unknown (My University, 2005)
Son yıllarda, küresel gemi adamları emek piyasası, küreselleşme ve bir dizi faktörün etkisiyle derin bir dönüşüm geçirmektedir. Bu dönüşüm emek piyasalarında istikrasızlık yarattığı gibi, çalışma şartlarının da kötüleşmesine yol açmıştır. Türkiye bunun bir istisnasını oluşturmamaktadır. Emek piyasası şartlarının değişmesi gelecek belirsizliğini artırdığı gibi, Türk gemi adamlarının ücretlerinin düşmesine ve çalışma şartlarının da kötüleşmesine yol açmıştır.

In recent years, global seafarers' labour markets have undergone substantial changes due to a number of factors along with globalization. These changes have created instability in the labour markets and resulted in deterioration in working conditions. Turkey is no exception to this. The changes in labour market conditions have not only made the future bleak but also led to the decrease in pay level and aggravation in working conditions of Turkish seafarers. Keywords: Seafarers, labour markets, shipping industry, simsar, working conditions, foreign flagged ship.
Keywords: İktisat; İşletme